Gender Mainstreaming In Glasses of Public Administration at Banten Province - Ipah Ema Jumiati (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Spirit Gender Mainstreaming (PUG) in Banten province began with the Banten Provincial Regulation No. 10 of 2005 on Gender Mainstreaming in Regional Development. Gender mainstreaming is a strategy that is done rationally and systematically to achieve gender equality in a number of aspects of human life through policies and programs that pay attention to the experience, aspirations, needs and problems of women and men into the planning, implementation, monitoring and evaluation of all policies and programs in various fields of life and development. PUG is carried out in accordance with Presidential Instruction No. 9 of 2000 on Gender Mainstreaming in National Development and Regulation of the Minister of Home Affairs Number 67 Year 2011 as the changes of Regulation No. 15 Year 2008 on Guidelines for Gender Mainstreaming in the Region. Unavailability of data disaggregated by sex in all sectors and accurate data on gender issues is an obstacle (for sectors and regions) to conduct a gender analysis is accurate. The impact was found obstacles in identifying gender issues in terms of aspects, roles, controls and benefits